Theoretical Experiments on Road Profile Data Analysis using Filter Combinations - Djoko Wahyu Karmiadji; M. Rosyidi; Tri Widodo; Harris Zaenal; Nofriyadi Nurdam; Andi M. Kadir; Sofwan Hidayat; Sahid Bismantoko; Nurhadi Pramana; Winarno Winarno (Automotive Experiences, 2023)
Identification of road profiles is needed to provide the input of automotive simulation and endurance testing. The analysis with estimation methods is mostly done to identify road profiles. The main goal of analysis methods is to obtain the data of vertical displacements due to road profile measurement. The acceleration data is obtained from measuring road profile by using 4 sensors of accelerometer placed on each car wheel. The measuring data is converted to be vertical displacement data by using a "double integrator", however, it is not easy to get accurate results since the signal obtained carries a lot of noise and it is necessary to design the right filter reduce the noise. In this study, the signal filtering methods reducing the noise were used Fast Fourier Transform (FFT) and Kalman Filter (KF) combination. Experiments were carried out by combining Fast Fourier Transform and Kalman Filters using an input signal with unit (volt) in the time domain. In addition, this research focused on preparing the survey data that has been obtained by eliminating the noise to convert becoming the displacement input data for providing the loads of automotive simulation testing.